PEMETAAN KONDISI FISIK JARINGAN IRIGASI DESA RASI RAYA KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA BERBASIS SISTEM INFORMASI GEOGRAFIS - Stevano F. X. Hariawan; David P. Rumambi; Sandra E. Pakasi (COCOS, 2019)
ABTRACTThe Lahendong Irrigation Network is located in Rasi Raya Village RatahanSubdistrict Southeast Minahasa Regency, which was established in 1971. In December 2013,damage to buildings and channels in the irrigation network. This research aims to make amap of physical conditions in the village of Rasi Raya, Ratahan District, Southeast MinahasaRegency, based on geographic information systems. This research was conducted in July2019-October 2019. The method is used in this research is imagery by using analysis fromGIS Software and measurements of the field. Lahendong Irrigation Network is geographicallyat 0°59'19.34"N-1°05'1.61"N (north latitude) and 124°44'27.66 "E-124°47'08.29"E (eastlongitude) altitude 225 – 340 meters above sea level, has an irigation network condition indexof 77.22% with an infrastructure weight of 34.75 out of a maximum value of 45, so periodicand routine maintenance was needed. The Lahendong Irrigation Network has an area of95.80 hectare and a channel of 9868 meters. Irrigation efficiency in the Lahendong IrrigationNetwork is 51.69% and water loss in the channel is 0.05 m3/second and evaporation is 3308mm/day. Lahendong Irrigation Network is presented in a spatial form namely Map ofLahendong Irrigation Network.Keywords : Physical Condition of Irigattion Network,Geographic Information System